Pengembangan Modul Pembelajaran Biologi Berbasis Discovery Learning Pada Materi Dunia Tumbuhan Kelas X SMA - Ananda, Adelia; Anas, Nirwana; Rohani, Rohani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The research that has been done is entitled “Development of Biology Learning Modules Based on Discovery Learning on Plant Material for Class X High School”. This study aims to develop teaching materials in the from of biology learning modules based on Discovery Learning on plant material that are valid, practical and effective. This study used the R&D research method with the ADDIE development model (analysis, design, development, implementation dan evaluation). The test subjects in this study were class X students of SMA Negeri 1 Pegajahan. The results of the assessment of the material and media expert validation test obtained an average percentage of 94,67% with a very valid category. The results of the practicality test assessment from the responses of educators and students obtained an average percentage of 87,77% in the very practical category. The results of the assessment of the effectiveness test obtained an average percentage of 0,67 in the medium category. Based on the results of testing the validity, practicality and effectiveness of the product, it can be concluded that the biology learning module based on Discovery Learning on the plant world material developed is valid use as additional teaching material for students in the biology learning process and can be used independently. Keywodrs: discovery learning based module, addie r&d model, plant world.